2021
DOI: 10.1002/joc.7421
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of gridded precipitation datasets for prospective hydrological applications in Sri Lanka

Abstract: The aim of this study was to assess the application of gridded precipitation datasets for applications in Sri Lanka and to identify suitable products that can be used for hydrological applications in data sparse regions. Here, nine global datasets were considered for this study, and after initial screening, four datasets, such as Integrated Multi-Satellite Retrievals for GPM (IMERG) early run calibrated, Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS), European Center for Medium range W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…The spatial and temporal resolution of IMERG.v6 is 0.1° × 0.1° and 30 min, respectively. The capability of both TMPA.v7 and IMERG.v6 have been validated by earlier studies against station observations and shown reasonable correlations for the rainfall variations over SL (Bandara et al, 2021;Huang et al, 2023;Perera et al, 2022;Yoshimoto & Amarnath, 2017). Due to the end of TMPA.v7 in 2019 and the availability of IMERG.v6 data starting in 2001, this study focused on the period from 2001 to 2019 for all analyses.…”
Section: Methodsmentioning
confidence: 67%
“…The spatial and temporal resolution of IMERG.v6 is 0.1° × 0.1° and 30 min, respectively. The capability of both TMPA.v7 and IMERG.v6 have been validated by earlier studies against station observations and shown reasonable correlations for the rainfall variations over SL (Bandara et al, 2021;Huang et al, 2023;Perera et al, 2022;Yoshimoto & Amarnath, 2017). Due to the end of TMPA.v7 in 2019 and the availability of IMERG.v6 data starting in 2001, this study focused on the period from 2001 to 2019 for all analyses.…”
Section: Methodsmentioning
confidence: 67%
“…Bandara et al. (2022) compared nine gridded precipitation datasets from reanalysis and remote sensing products for meteorological and hydrological applications in Sri Lanka. They inferred that ERA5 had the best performance since it replicated the observed precipitation climatology of Sri Lanka very well.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the precipitation threshold for an extreme precipitation event is 15.6 mm day −1 , and extreme precipitation events occurred on 694 of 13,880 days in the analysis period. Bandara et al (2022) compared nine gridded precipitation datasets from reanalysis and remote sensing products for meteorological and hydrological applications in Sri Lanka. They inferred that ERA5 had the best performance since it replicated the observed precipitation climatology of Sri Lanka very well.…”
Section: Era5 Reanalysismentioning
confidence: 99%